Impact of a health literacy intervention combining general practitioner training and a consumer facing intervention to improve colorectal cancer screening in underserved areas: protocol for a multicentric cluster randomized controlled trial - Marie-Anne Durand; Aurore Lamouroux; Niamh M. Redmond; Michel Rotily; Aurélie Bourmaud; Anne-Marie Schott; Isabelle Auger-Aubin; Adèle Frachon; Catherine Exbrayat; Christian Balamou; Laëtitia Gimenez; Pascale Grosclaude; et al. (BMC, 2021)
Abstract Background Colorectal cancer (CRC) is a leading cause of cancer burden worldwide. In France, it is the second most common cause of cancer death after lung cancer. Systematic uptake of CRC screening can improve survival rates. However, people with limited health literacy (HL) and lower socioeconomic position rarely participate. Our aim is to assess the impact of an intervention combining HL and CRC screening training for general practitioners (GPs) with a pictorial brochure and video targeting eligible patients, to increase CRC screening and other secondary outcomes, after 1 year, in several underserved geographic areas in France. Methods We will use a two-arm multicentric randomized controlled cluster trial with 32 GPs primarily serving underserved populations across four regions in France with 1024 patients recruited. GPs practicing in underserved areas (identified using the European Deprivation Index) will be block-randomized to: 1) a combined intervention (HL and CRC training + brochure and video for eligible patients), or 2) usual care. Patients will be included if they are between 50 and 74 years old, eligible for CRC screening, and present to recruited GPs. The primary outcome is CRC screening uptake after 1 year. Secondary outcomes include increasing knowledge and patient activation. After trial recruitment, we will conduct semi-structured interviews with up to 24 GPs (up to 8 in each region) and up to 48 patients (6 to 12 per region) based on data saturation. We will explore strategies that promote the intervention's sustained use and rapid implementation using Normalization Process Theory. We will follow a community-based participatory research approach throughout the trial. For the analyses, we will adopt a regression framework for all quantitative data. We will also use exploratory mediation analyses. We will analyze all qualitative data using a framework analysis guided by Normalization Process Theory. Discussion Limited HL and its impact on the general population is a growing public health and policy challenge worldwide. It has received limited attention in France. A combined HL intervention could reduce disparities in CRC screening, increase screening rates among the most vulnerable populations, and increase knowledge and activation (beneficial in the context of repeated screening). Trial registration Registry: ClinicalTrials.gov. Trial registration number: 2020-A01687-32 . Date of registration: 17th November 2020.